Adjuvant oncolytic virotherapy for personalized anti-cancer vaccination - D. G. Roy (Nature Portfolio, 2021)
Viruses expressing tumour antigens can prime and boost anti-tumour immunity but the efficiency of this approach depends on the capacity of the virus to infect the host. Here, the authors show that vaccination with oncolytic viruses co-administered with tumour antigenic peptides is as efficient as antigen-engineered oncolytic viruses.